Pengembangan Media Pembelajaran Petualangan Si RAMA dengan Augmented Reality untuk Meningkatkan Literasi Sains Siswa Sekolah Dasar - Lusiana Arie Wijayanti; Wahyudi Wahyudi (Pusat Riset dan Inovasi Nasional, 2025)
Science literacy is an important 21st century competency, but Indonesian students' ability in this aspect is still low. Based on PISA results, Indonesia is ranked 68th, with only 34.16% of students reaching level 2, far below the OECD average of 75.51%. One of the factors causing this is the lack of variety of learning media used by teachers. This study aims to describe the development process, validity, effectiveness, and practicality of the Adventure of Si RAMA with Augmented Reality media in improving the science literacy of elementary school students. The research used the Research and Development (R&D) method with the ADDIE model. The stages in this development research include identification of potential and problems, analysis, product design, design development and product validation, product revision, product trials, and evaluation. The validation results showed very high scores from material experts (90%), learning design (94%), and media (95 The effectiveness of the media is seen from the T Test results which resulted in a sig. value of 0.000, which is smaller than 0.05, which indicates that this media is effective in improving science literacy. Practicality assessment from students reached 89% and from teachers 92%, both of which were in the very practical category. Thus, this media is worth using as an innovative learning alternative to support the improvement of science literacy in elementary schools.